A highly sensitive fluorescent light-up probe for real-time detection of the endogenous protein target and its antagonism in live cells1. Issue 29 (7th August 2015) - Geng, Junlong; Goh, Walter L.; Zhang, Chongjing; Lane, David P.; Liu, Bin; Ghadessy, Farid; Tan, Yen Nee
<x xml:space="preserve">Abstract</x> A target-specific switchable fluorescent probe for cellular Mdm2 protein detection (off–on) and drug discovery applications (on–off) targeting the p53 pathway.